Implikasi Media Terhadap Dinamika Partisipasi Politik Di Era Digital - Aldy Ardiansyah Purwono Putra; Dewi Kurniasari; Adhim, Mohammad Nasrun; Widodo Pujo Laksono; Yunita Dwi Pristiani (Philosophiamundi, 2024)
This case study discusses the implications of media on the dynamics of political participation in the digital era. Media plays an important role in shaping the dynamics of political participation. Technological developments have changed the way people interact with political information and government. The digital era affects political engagement in society. The findings from this study are expected to provide in-depth insights into the role of media in shaping the dynamics of political participation, as well as its implications for political governance and society as a whole. This study is expected to contribute to formulating relevant policies in facing the challenges of political participation in the digital era. This study uses data collection methods to analyze the implications of media on the dynamics of political participation. Data were collected through interviews with respondents, and social media content analysis to understand the patterns of political participation in a digital context. The results of the study show that digital media has a significant impact on the dynamics of political participation. Changes in participation patterns were found, including increased participation through social media and changes in public perceptions of politics due to continuous exposure to political information on digital media. The implications of these findings require special attention in designing policies and strategies for political communication in the digital era.